Does Full-Day Kindergarten Reduce Parenting Daily Hassles? - Stover, Katherine; Pelletier, Janette (Canadian Journal of Education/Revue canadienne de l’éducation, 2018)
Parenting daily hassles are viewed as the recurring demands associated with raising a young child (Crnic & Greenberg, 1990) and contribute to parental well-being and parenting relationships (Crnic, Gaze, & Hoffman, 2005). The goal of this study was to examine differences in the daily hassles reported by parents of half-day and full-day kindergarten students following the phased-in implementation of full-day kindergarten in Ontario. Based on results from a previous demonstration project of integrated kindergarten and childcare, it was hypothesized that parents of full-day kindergarten children would experience fewer daily hassles related to education and childcare. Four hundred and forty-nine parents participating in a longitudinal study tracking Ontario’s transition from half-day to full-day kindergarten were asked to complete a survey of their experiences with early childhood parenting daily hassles, as well as ademographic questionnaire as part of the larger study. We investigated whether parents of children enrolled in full-day programs experienced reductions in parenting daily hassles as compared to parents of children in half-day programs. Overall, parents of children enrolled in full-day kindergarten reported similar levels of daily hassles to parents of children in half-day programs. Additional analyses of demographic factors indicated that full-day kindergarten was related to lower levels of daily hassles for parents who worked full-time. Policy implications regarding integrated full-day kindergarten and childcare are discussed.